A new record of Schendyloides alacer (Pocock, 1891) from the Falkland Islands and a redescription of the species (Chilopoda Geophilomorpha) - Pereira, Luis Alberto (1992)
Original as well as subsequent descriptions of the geophilomorph centipede Schendyloides alacer (Pocock, 1891) are quite unsatisfactory and incomplete. Therefore, we seize here the opportunity to supplement them with data originating from new material of this species recently examined by us. This study has been prompted by the examination of a specimen collected in the Falkland Islands by Prof. (Emeritus) A. Macfadyen (Coleraine, Northern Ireland) who recently sent it to one of us (LAP) for identification. We have compared this specimen, as well as the additional ones from Southern Argentina, with the type series of Scolioplanes magellanicus Attems, 1897, which we regard as a synonym of Pocock’s species, alongwith Crabill’s (1964) lines. Both nominal species were described from the Straits of Magellan region. Both Pocock’s and Attems’s type material was checked by Crabill before synonymyzing magellanicus with alacer.